2001
DOI: 10.1093/sw/46.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Client Violence

Abstract: Much has been written about client violence against social workers; however, little attention has been given to reporting behavior of social workers who have been the target of such violence. The study discussed in this article documents the prevalence of client violence among a sample of social workers from a broad range of social work settings. It examines respondents' reasons for not reporting or for reporting client violence to management. A random sample of 300 social workers was mailed a questionnaire th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 6 publications
6
76
0
3
Order By: Relevance
“…In another study, he found that 18% of such workers had been physically assaulted during their working career (Bowie, 1996). In North America, high rates of violence against social work staff were reported by Macdonald and Sirotich (2001), Jayaratne, Vinokur-Kaplan, Nagda, and Chess (1995), and Tully, Kropf, and Price (1993), with studies from other countries such as Iran (Padyab, Chelak, Nygren, & Ghazinour, 2012) also addressing this as a problematic area for social workers.…”
Section: Child Protectionmentioning
confidence: 99%
“…In another study, he found that 18% of such workers had been physically assaulted during their working career (Bowie, 1996). In North America, high rates of violence against social work staff were reported by Macdonald and Sirotich (2001), Jayaratne, Vinokur-Kaplan, Nagda, and Chess (1995), and Tully, Kropf, and Price (1993), with studies from other countries such as Iran (Padyab, Chelak, Nygren, & Ghazinour, 2012) also addressing this as a problematic area for social workers.…”
Section: Child Protectionmentioning
confidence: 99%
“…Although these figures appear quite high, a variety of studies indicate that the incidence of occupational violence is under-reported (Barrett, 1997;Gates, 1995;Le Mar, Gerberich, Lohman & Zaidman, 1998;Macdonald, Sirotich, 2001;Rowett, 1986;Crane 1986). This may be particularly the case in health care settings for two major reasons, the first reason being that violence is seen by many health professionals as part of everyday professional life.…”
Section: Under-reporting Of Violencementioning
confidence: 99%
“…Au plan individuel, l'ÉSPT s'avère être la conséquence psychologique la plus commune (Lanctôt et Guay, 2014). L'évaluation de la prévalence de ce phénomène devient essentielle, car le développement et le déploiement de stratégies de prévention et de soutien aux victimes sont tributaires d'une mesure plus adaptée (ou sensible) de la violence en milieu de travail (Dyrkacz, Mak et Heck, 2012;Macdonald et Sirotich, 2001). …”
Section: Selon La Commission Des Normes De L'équité De La Santé Et unclassified